2023
DOI: 10.3389/fmed.2023.1122405
|View full text |Cite
|
Sign up to set email alerts
|

Enabling technologies driving drug research and development

Abstract: One of the strategic goals of the European Medicines Agency (EMA) and the European Medicines Regulatory Network is to support the research and uptake of innovative methods and technologies in the development of medicines. To promote this goal, EMA drew up a list of enabling technologies (ETs), which are novel and fast-growing technologies that have the potential to enable innovation and therefore exert considerable impact on drug development. In this work, enabling technologies identified by the EMA are analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…43,44 The fact that innovative trial designs are not used for development of these medicines more often may be due to the challenges in the planning of these studies, but also in their regulatory assessment. 45 A study of Vass et al 46 showed that novel clinical trial methodologies are, however, the predominant "enabling technology" mentioned in recent EMA procedures, such as the Qualification of Novel Methodologies or Scientific Advice procedures and Innovation Task Force meetings. However, the issued discussed and insights gained during these procedures remain confidential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…43,44 The fact that innovative trial designs are not used for development of these medicines more often may be due to the challenges in the planning of these studies, but also in their regulatory assessment. 45 A study of Vass et al 46 showed that novel clinical trial methodologies are, however, the predominant "enabling technology" mentioned in recent EMA procedures, such as the Qualification of Novel Methodologies or Scientific Advice procedures and Innovation Task Force meetings. However, the issued discussed and insights gained during these procedures remain confidential.…”
Section: Discussionmentioning
confidence: 99%
“…According to the same study, novel biomarkers are more prevalent hits in a PubMed search as compared to a search in the selected EMA procedures or clinical trial registrations. 46 One explanation could be that novel biomarkers are being investigated widely, but have not reached the clinical stage yet. Transparent communication and collaboration between regulators and biomarker developers is essential to move these early developments forward, by sharing information and increase common understanding of evidentiary standards that govern the use of biomarkers in medicine development programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations